P361 Prevalence of bacterial vaginosis among women attending sexual health clinics in new york city, 2017–2018. (14th July 2019) - Davis, Alissa; Pathela, Preeti; Crawley, Addie; Schillinger, Julia
Abstract : Background: Bacterial vaginosis (BV) is a common condition among women and is associated with HIV/STI acquisition and adverse pregnancy outcomes. We describe the prevalence of BV diagnoses and repeat BV diagnoses among women attending New York City (NYC) public sexual health clinics (SHC) and examine demographic characteristics associated with BV. Methods: Using electronic medical record data for patients who were assigned female sex at birth ("women"), we identified BV diagnoses made during clinician visits at NYC SHC during January 2017–April 2018, and recurrent BV during a six-month follow-up period through October 2018. BV diagnosis was defined as a physician diagnosis of BV with a vaginal pH ≥4.5, and positive whiff-amine test. We used chi-square tests to compare characteristics of women with and without a BV diagnosis. Results: Of 13, 153 women with ≥ 1 visits to the SHC, 34% (4, 449) were diagnosed with BV. There were significant differences in BV prevalence by race/ethnicity: 39.5% (95% CI: [38.7–40.3%]) of non-Hispanic black women versus 29.6% ([28.3–30.9%]) Hispanic, 21.2% ([19.1–23.3%]) non-Hispanic white, and 19.7% ([16.5–22.9%]) non-Hispanic Asian women. Women of HIV-negative/unknown HIV status had higher BV prevalence than HIV-positive women (33.9% vs 23.4%, p=0.02). Women reporting sex with both men and women had higher BV prevalence (42.0%, 95% CI: [37.5–46.5%]) than women reporting sex with men only (34.5%, [34.2–34.8%]) or women reporting sex with women only (28.1%, [22.2–34.0%]). Among women with BV, 4, 404 (99%) received treatment and 1588 (36.1%) of those had another clinician visit within 6 months. Among returning women, 282 (17.8%) were given another BV diagnosis within 3 months, and 601 (37.8%) within 6 months. Conclusion: One-third of women attending NYC SHC were diagnosed with BV, and recurrent BV was common. Additional research is needed to identify effective therapies to reduce the high prevalence and recurrence rates of BV. Disclosure: No significant relationships.